Evaluation of Sustained Virologic Response as a Relevant Surrogate Endpoint for Long-term Outcomes of Hepatitis C Virus Infection. (13th February 2020) - Krassenburg, Lisette A P; Zanjir, Wayel R; Georgie, Firas; Stotland, Emily; Janssen, Harry L A; Hansen, Bettina E; Feld, Jordan J
Abstract: Background: The causal link of sustained virologic response (SVR) with outcome has been challenged. With improved SVR rates with direct-acting antivirals (DAAs), the benefit of SVR would be expected to diminish if the association with outcome is not causal. Methods: Data were collected for patients starting treatment with interferon (IFN) or DAAs between June 2006 and December 2016. To control for disease severity, criteria for the IDEAL (Individualized Dosing Efficacy vs. Flat Dosing to Assess Optimal Pegylated Interferon Therapy) trial determined IFN-eligibility. Clinical events were decompensation, hepatocellular carcinoma, liver transplantation, and all-cause mortality. Results: In 1078 IDEAL-eligible patients, 1306 treatments occurred (52% IFN, 49% DAAs). Cirrhosis was present in 30% DAAs vs 21% IFN ( P < .001). SVR was 97% with DAAs vs 52% with IFN ( P < .0001). The 24-month cumulative event-free survival was 99% for IFN and 97% for DAAs with SVR ( P = .08) and 96% and 75%, respectively, for non-SVR ( P = .01). SVR was associated with improved event-free survival with an adjusted hazard ratio of 0.21 (95% confidence interval, .06–.71; P = .01). Using inverse probability of treatment weighting to match IFN nonresponders with DAA-treated patients, the 24-month event-rate was 1.1% with DAAs compared to 3.4% in IFN nonresponders ( P = .005), highlighting the clinical benefit of maximizing SVR. Conclusions: In IFN-eligible patients, SVR is more commonly achieved with DAAs and confers a similar clinical benefit as in those treated with IFN. The reduced event-rate with DAAs compared to IFN, despite similar disease severity, confirm that SVR alters prognosis leading to improved clinical outcomes. Abstract : Patients likely to have failed therapy with interferon achieved high rates of sustained virologic response (SVR) with the same clinical benefit as others achieving SVR, indicating that SVR indeed changes prognosis and is thus a valid surrogate endpoint.